MicroRNA-124 mediates the cholinergic anti-inflammatory action through inhibiting the production of pro-inflammatory cytokines - Sun, Yang; Li, Qi; Gui, Huan; Xu, Dong-Ping; Yang, Yi-Li; Su, Ding-Feng; Liu, Xia (Cell research, 2013)
The vagus nerve can control inflammatory response through a ＇cholinergic anti-inflammatory pathway＇, which is mediated by the α7-nicotinic acetylcholine receptor （α7nAChR） on macrophages. However, the intracellular mechanisms that link a7nAChR activation and pro-inflammatory cytokine production remain not well understood. In this study, we found that miR-124 is upregulated by cholinergic agonists in LPS-exposed cells and mice. Utilizing miR-124 mimic and siRNA knockdown, we demonstrated that miR-124 is a critical mediator for the cholinergic anti-inflammatory action. Furthermore, our data indicated that miR-124 modulates LPS-induced cytokine production by targeting signal transducer and activator of transcription 3 （STAT3） to decrease IL-6 production and TNF-o converting enzyme （TACE） to reduce TNF-α release. These results also indicate that miR-124 is a potential therapeutic target for the treatment of inflammatory diseases.